1987
DOI: 10.1093/nar/15.10.3947
|View full text |Cite
|
Sign up to set email alerts
|

The white gene as a marker in a new P-element vector for gene transfer inDrosophila

Abstract: We describe new vectors suitable for P-element mediated germ line transformation of Drosophila melanogaster using passenger genes whose expression does not result in a readily detectable phenotypic change of the transformed flies. The P-element vectors contain the white gene fused to the heat shock protein 70 (hsp70) gene promoter. Expression of the white gene rescues the white phenotype of recipient flies partly or completely even without heat treatment. Transformed descendents of most founder animals (GO) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
180
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 360 publications
(181 citation statements)
references
References 36 publications
0
180
0
1
Order By: Relevance
“…The addition of a FLAG epitope (Kodak) to the N terminus of the Hrb87F cDNA has been described (Zu et al+, 1996)+ pBS-HRB87F was generated by inserting the 2+2 kb EcoR1 fragment containing FLAG-Hrb87F cDNA into pBluescript II KS(ϩ) (Stratagene) which had been modified to remove the Hinc II site in the polylinker sequence+ pBS-HRB87F was used to make the following mutant constructs+ The sequence of each construct was confirmed by DNA sequencing, and in those cases where new restriction sites were introduced, by restriction digestion+ pBS-X-R2-G, which contains Asp substitutions of both Phe 67 and Phe 69 in RNP1 of RBD-1, was constructed by the mega-primer PCR technique (Sarkar & Sommer, 1990)+ Mega-primer #1 was made using primer #1 (59 GCCTGAAG GCTCACTTCGAG) and primer #2 (59 GACTGGGAGTACGT GATATCACCGTCGCCGCGAGAGCGCTTCG), which converted two TTC codons for Phe to codons GAT and GAC for Asp and also created an EcoRV site+ A second PCR reaction using mega-primer #1 and primer #4 (59 TTGTTCTTGATG GAGTGGG) resulted in a fragment that was used to substitute the 354-bp Hinc II fragment of the wild type cDNA in pBS-HRB87F+ pBS-R1-X-G, which contains Asp substitutions of both Phe 158 and Phe 160 in RNP1 of RBD-2, was generated in a similar approach+ Mega-primer #2 was made using primer #3 (59 CCGGCAAGAAGCGCGGCGACGCCGACATTGAG TTGCATGACTAC) and primer #4 and the second PCR reaction used mega-primer #2 and primer #1+ pBS-X-X-G, which contains Asp substitutions of all 4 conserved Phe residues in both RBD-1 and RBD-2, was generated by substituting the 2+3-kb BsaA I fragment of pBS-X-R2-G, which spans RBD-2, with the same BsaA I fragment from pBS-R1-X-G+ pBS-R1-R2, the carboxyl terminal glycine-rich domain deletion mutant (amino acids 1-195), was constructed by deleting the terminal 1+5-kb BsaB I/Spe I fragment of Hrb87F cDNA+ The junction sequence contained an in-frame stop codon and a new EcoR V site+ pBS-R1-R2-RS, which encodes a chimeric protein of HRB87F and B52, was made by joining the two RBDs of HRB87F (amino acids 1-196) to the carboxyl terminal RS domain (amino acids 186-376) of Drosophila B52 (dSRp55; Champlin et al+, 1991)+ The RS domain of B52 was obtained by isolating the 0+9-kb BamH I/Spe I fragment from pBS-B52 (kindly provided by J+ Lis, Cornell)+ After filling in the 59 overhang of the BamH I site, the fragment was used to replace the 1+5-kb BsaB I/Spe I from pBS-HRB87F, which contains the sequence encoding the GRD+ pBHS/K(Ϫ) (Park et al+, 1994; kindly provided by P+ Adler, University of Virginia) was used to generate intermediate plasmids for each mutant cDNA+ The 2+2-kb EcoR I fragments of pBS-HRB87F, pBS-R1-X-G, pBS-X-R2-G, and pBS-X-X-G containing the wild-type or mutant cDNAs were inserted into the EcoR I site between the Drosophila Hsp70 promoter and the SV40 polyadenylation signal of pBHS/K(Ϫ)+ The 0+7-kb Xho I/Xba I fragment of pBS-R1-R2 was inserted into the EcoR I site of pBHS/K(Ϫ) after filling the 59 overhangs of Xho I, Xab I, and EcoR I sites+ The 1+6-kb EcoR I fragment of pBS-R1-R2-RS was inserted into the EcoR I site of pBHS/ K(Ϫ)+ The Not I/Kpn I fragments from the pBHS/K(Ϫ) plasmid series containing epitope-tagged Hrb87F wild-type and mutant cDNAs under the control of the Hsp70 promoter and ending with the SV40 polyA signal were subcloned into the P-element transformation vector pW8 (Klemenz et al+, 1987)+ P-element mediated transformation was done by standard techniques (Roberts, 1986;Zu et al+, 1996)+ Genetic crosses indicated that each stable homozygous line had an insert on a single chromosome...…”
Section: Methodsmentioning
confidence: 99%
“…The addition of a FLAG epitope (Kodak) to the N terminus of the Hrb87F cDNA has been described (Zu et al+, 1996)+ pBS-HRB87F was generated by inserting the 2+2 kb EcoR1 fragment containing FLAG-Hrb87F cDNA into pBluescript II KS(ϩ) (Stratagene) which had been modified to remove the Hinc II site in the polylinker sequence+ pBS-HRB87F was used to make the following mutant constructs+ The sequence of each construct was confirmed by DNA sequencing, and in those cases where new restriction sites were introduced, by restriction digestion+ pBS-X-R2-G, which contains Asp substitutions of both Phe 67 and Phe 69 in RNP1 of RBD-1, was constructed by the mega-primer PCR technique (Sarkar & Sommer, 1990)+ Mega-primer #1 was made using primer #1 (59 GCCTGAAG GCTCACTTCGAG) and primer #2 (59 GACTGGGAGTACGT GATATCACCGTCGCCGCGAGAGCGCTTCG), which converted two TTC codons for Phe to codons GAT and GAC for Asp and also created an EcoRV site+ A second PCR reaction using mega-primer #1 and primer #4 (59 TTGTTCTTGATG GAGTGGG) resulted in a fragment that was used to substitute the 354-bp Hinc II fragment of the wild type cDNA in pBS-HRB87F+ pBS-R1-X-G, which contains Asp substitutions of both Phe 158 and Phe 160 in RNP1 of RBD-2, was generated in a similar approach+ Mega-primer #2 was made using primer #3 (59 CCGGCAAGAAGCGCGGCGACGCCGACATTGAG TTGCATGACTAC) and primer #4 and the second PCR reaction used mega-primer #2 and primer #1+ pBS-X-X-G, which contains Asp substitutions of all 4 conserved Phe residues in both RBD-1 and RBD-2, was generated by substituting the 2+3-kb BsaA I fragment of pBS-X-R2-G, which spans RBD-2, with the same BsaA I fragment from pBS-R1-X-G+ pBS-R1-R2, the carboxyl terminal glycine-rich domain deletion mutant (amino acids 1-195), was constructed by deleting the terminal 1+5-kb BsaB I/Spe I fragment of Hrb87F cDNA+ The junction sequence contained an in-frame stop codon and a new EcoR V site+ pBS-R1-R2-RS, which encodes a chimeric protein of HRB87F and B52, was made by joining the two RBDs of HRB87F (amino acids 1-196) to the carboxyl terminal RS domain (amino acids 186-376) of Drosophila B52 (dSRp55; Champlin et al+, 1991)+ The RS domain of B52 was obtained by isolating the 0+9-kb BamH I/Spe I fragment from pBS-B52 (kindly provided by J+ Lis, Cornell)+ After filling in the 59 overhang of the BamH I site, the fragment was used to replace the 1+5-kb BsaB I/Spe I from pBS-HRB87F, which contains the sequence encoding the GRD+ pBHS/K(Ϫ) (Park et al+, 1994; kindly provided by P+ Adler, University of Virginia) was used to generate intermediate plasmids for each mutant cDNA+ The 2+2-kb EcoR I fragments of pBS-HRB87F, pBS-R1-X-G, pBS-X-R2-G, and pBS-X-X-G containing the wild-type or mutant cDNAs were inserted into the EcoR I site between the Drosophila Hsp70 promoter and the SV40 polyadenylation signal of pBHS/K(Ϫ)+ The 0+7-kb Xho I/Xba I fragment of pBS-R1-R2 was inserted into the EcoR I site of pBHS/K(Ϫ) after filling the 59 overhangs of Xho I, Xab I, and EcoR I sites+ The 1+6-kb EcoR I fragment of pBS-R1-R2-RS was inserted into the EcoR I site of pBHS/ K(Ϫ)+ The Not I/Kpn I fragments from the pBHS/K(Ϫ) plasmid series containing epitope-tagged Hrb87F wild-type and mutant cDNAs under the control of the Hsp70 promoter and ending with the SV40 polyA signal were subcloned into the P-element transformation vector pW8 (Klemenz et al+, 1987)+ P-element mediated transformation was done by standard techniques (Roberts, 1986;Zu et al+, 1996)+ Genetic crosses indicated that each stable homozygous line had an insert on a single chromosome...…”
Section: Methodsmentioning
confidence: 99%
“…These constructions have been described in detail (Wojtas 1996). P-element transformation was conducted using a standard protocol (Rubin and Spradling 1982) and the vector pw8 (Klemenz, et al, 1987). Transformants, w+ flies, were characterized for GPDH content using Western blots and histochemical staining of dissected tissues (Skuse and Sullivan, 1985;von Kalm et al, 1989).…”
Section: Transformationmentioning
confidence: 99%
“…P elements, naturally occurring transposable elements in Drosophila, can be modified to carry transgenes (Rubin and Spradling 1983) and used for mutagenesis by inserting into genomic regions (Cooley et al 1998a,b). The white mutant background is commonly used for insertion of transgenes that carry a cDNA sequence of the wild-type white gene, mini-white (w 1mC ), which serves as a positive marker of transgene incorporation (Klemenz et al 1987). One copy of w 1mC is sufficient to induce red eye development in a white homozygous mutant, although the degree of pigmentation may vary depending on insertion position.…”
mentioning
confidence: 99%